COMPUTER-AIDED TOOLS TO ASSESS STUDENTS' PROFESSIONAL LANGUAGE SKILLS - Svetlana Barsuk (Kherson State University, 2016)
Traditional teaching aids to develop students' language skills are a coursebook, a tape recorder, an audio CD or a video. With a development of new technologies and opportunities they provide, teachers and students should not limit their cooperation to classroom activities only. To develop critical thinking, train learning strategies, and increase students' autonomy in their attempts to practise English outside the classroom computer-aided language learning is an available instrument, that can provide an additional learning environment for both students and teachers, enhance language learning through involving additional resources. Computer-based language courses supply learners with plenty of language learning and professionally oriented materials and allow student to work at their own pace. Computer-aided tools can be used to reinforce the students' language skills through additional practice or as a remedial tool to complete gaps in students' knowledge. The author of the article describes her own experience of utilizing computer-based aids to test the knowledge of seamanship and language skills of the future deck officers